World economic geography - White, C. Langdon; Griffin, Paul F.; McKnight, Tom L. (Belmont, California : Wadsworth Pub. Co., 1964)
This textbook approaches economic geography by commodity, because experience has proved that this is the most effective and most interesting way of presenting the subject. The book covers the following: The World's Mineral and Energy Resources; The World's Industries; The World's Foods; Some Nonfood Crops; The World's Fibers and Vegetable Oils; The World's Non-mineral Extractive Industries and The World's Transportation.
Includes bibliographical references and index.
aia 2/11/2017
Loans
Keywords: Economic geography